ANALYSIS CARRYING CAPACITY AGRICULTURAL IN KUBU RAYA DISTRICT - Permadi, Ganang; A Yusra, Abdul Hamid; Imelda, Imelda (Jurnal Sains Mahasiswa Pertanian, 2019)
This research was conducted to determine the carrying capacity of agricultural land in Kubu Raya Regency. The research method used in this research is the survey method, the determination of the research location is done intentionally (purposive). The data collected in this research is secondary data. The method of data analysis using the analysis of Odum, Christaller, Ebenezer Howard and Issad in Moniaga, 2011. The results showed that, Kubu Raya District is capable of self-supporting food but has not been able to provide a decent life for its residents Kubu Raya Regency can still be self-sufficient but unable to meet the needs physical population. Therefore, these problems must be overcome. This is done by applying sustainable agriculture and appropriate land use by treating it as needed, so that the soil is not damaged and can guarantee high productivi